2018
DOI: 10.12816/0044677
|View full text |Cite
|
Sign up to set email alerts
|

Parental Awareness regarding Aerodigestive Pediatric Foreign Bodies, Eastern Province, Saudi Arabia

Abstract: Background: Aerodigestive foreign bodies are common clinical problem that may lead to life threatening complications or sudden death. It's commonly seen in children since they are curious to explore environmental objects with their mouth, while the development of airway protection reflexes and chewing capacity are immature. Objectives: This study aims to assess the extent of parents' awareness about the danger of foreign objects that can be swallowed or inhaled by their children and how to manage such cases. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Among the 1087 parents surveyed, our results showed a poor level of knowledge and low level of FBA practices (65.4% and 78.6%, respectively), which agrees with a similar study conducted in Al Qassim region [4] Their participants had poor knowledge of FBA (63.1%) and poor FBA practices (55.3%), whereas another study carried in the eastern province of Saudi Arabia reported a high level of awareness (60.3%) about aerodigestive foreign bodies in pediatrics [15]. In comparison to the eastern province study, which aimed to evaluate parents' awareness of the risk of aerodigestive foreign bodies in children, our study expanded the scope to assess the FBA practices and knowledge of FBA of parents.…”
Section: Discussionsupporting
confidence: 88%
“…Among the 1087 parents surveyed, our results showed a poor level of knowledge and low level of FBA practices (65.4% and 78.6%, respectively), which agrees with a similar study conducted in Al Qassim region [4] Their participants had poor knowledge of FBA (63.1%) and poor FBA practices (55.3%), whereas another study carried in the eastern province of Saudi Arabia reported a high level of awareness (60.3%) about aerodigestive foreign bodies in pediatrics [15]. In comparison to the eastern province study, which aimed to evaluate parents' awareness of the risk of aerodigestive foreign bodies in children, our study expanded the scope to assess the FBA practices and knowledge of FBA of parents.…”
Section: Discussionsupporting
confidence: 88%
“…[ 15 ] They found that 59% of mothers had poor knowledge, 28% were average, and only 13% had good knowledge regarding FBA. On the other hand, AlShakhs et al .,[ 16 ] reported conflicting findings. Their reports indicated that the awareness toward aerodigestive pediatric foreign bodies was high (60.3%) however, only 36.2% reported to have awareness regarding its management which was not consistent with our reports.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Esophageal FB is commonly observed in children, as their lack of molars and curiosity may lead to the placement of the FBs in the mouth. 1 , 2 According to Abualenain et al, 1 most FB ingestion occurs in children aged 0–4 years. Moreover, variations in incidence have been observed between male and female patients.…”
mentioning
confidence: 99%